Rhetoric's pragmatism : essays in rhetorical hermeneutics - Mailloux, Steven (RSA series in transdisciplinary rhetoric., 2017)
"A collection of essays on the methodology of rhetorical hermeneutics. Takes a historically and theoretically informed approach to textual interpretation, focusing on the production, circulation, and reception of written and performed communication"--Provided by publisher